2013
DOI: 10.1080/00224499.2012.702799
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Aggression among Brazilian College Students: Prevalence of Victimization and Perpetration in Men and Women

Abstract: Despite the increased attention devoted to sexual aggression among college students in the international research literature, Brazil has no systematic studies on the prevalence of sexual aggression in college populations. The present research measured the prevalence of sexual aggression and victimization since age 14 among 742 first-year college students in Brazil (411 women). A Portuguese version of the Short Form of the Sexual Experiences Survey (Koss et al., 2007 ) was administered to collect information fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
3
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 58 publications
3
18
3
8
Order By: Relevance
“…Nearly 70% of adult rape cases occurred between 6:00 PM and 6:00 AM. These data differ sharply from those provided by studies in the general population or convenience samples, where both women and men report sexual victimization by intimate partners, occurring in domestic settings, and where other forms of coercion were applied (e.g., taking advantage of victim's incapacitated state) 13,14 . Besides the underreporting problem, the IPEA report did not included victims treated at private clinics, which mainly serve the middle and upper classes in Brazil.…”
contrasting
confidence: 48%
See 4 more Smart Citations
“…Nearly 70% of adult rape cases occurred between 6:00 PM and 6:00 AM. These data differ sharply from those provided by studies in the general population or convenience samples, where both women and men report sexual victimization by intimate partners, occurring in domestic settings, and where other forms of coercion were applied (e.g., taking advantage of victim's incapacitated state) 13,14 . Besides the underreporting problem, the IPEA report did not included victims treated at private clinics, which mainly serve the middle and upper classes in Brazil.…”
contrasting
confidence: 48%
“…The highest previous-year incidence rate was reported by a sample of university students (38.5% in women and 34.5% in men) 38 . Three other studies also reported high victimization rates in university students 14,39,40 .…”
Section: • Regionmentioning
confidence: 96%
See 3 more Smart Citations